Hematological malignancies in adults with a family predisposition - Bochtler, Tilmann; Haag, Georg Martin; Schott, Sarah; Kloor, Matthias; Krämer, Alwin; Müller-Tidow, Carsten (Deutsches Ärzteblatt, 2018)
The significance of hereditary cancer predisposition syndromes has been established for solid tumors, such as the Lynch syndrome or familial breast and ovarian cancer, and raised awareness of the role of hereditary predisposition in other cancer...